EXTRACTION OF ALUMINA FROM BAUXITE RESIDUE FOR PREPARATION OF ALUMS AND POLY ALUMINUM CHLORIDE - MUCHTAR AZIZ; AGUS Wahyudi (Indonesian Mining Journal, 2010)
The chemical composition of West Kalimantan bauxite is 45 pct Al2O3 and 16 pct Fe2O3 that has been extracted to produce alumina and bauxite residue (red mud). The residues contains Al2O3 20 pct and Fe2O3 about 37 pct, wich was furthermore processed by roasting or lime-soda sinterization at temperature of 800- 1100°C. The sintered product was leached with sodium carbonate solution to produce soluble sodium aluminate (2NaAlO2). The solution obtained was then precipitated to produce hydrated alumina (Al(OH)3. Hydrated alumina was then sulfateized by adding ammonium hydroxide, and followed by crystallization to produce high purity of ammonium aluminum sulfate crystals (alums). In addition, hydrated alumina was also chlorinated in stoichiometric amount at mol ratio of OH/Al = 0.5 – 1.5 to form polyaluminum chloride (PAC). The residue obtained from leaching was concentrated by 1000 gauss of magnetic separator to produce iron concentrate as a by product. As the results, sulfatation of hydrated alumina with addition of ammonium hydroxide results high grade of ammonium aluminum sulfate (NH4Al(SO4)2 .12H2O) crystals. Chlorination of hydrated alumina in stoichiometric amount at mol ratio of OH/Al = 1.0 results polyaluminum chloride (PAC) that quality is adjacent to the first type of PAC. Through the soda-lime sinter process, it can also produce iron concentrate having grade of 66 % Fe2O3 with 40 % of recovery